Study on readmission to a Tertiary Care Women Hospital (Castle Street Hospital for Women in year - 2005 ) in Sri Lanka - Guruge, B.A.H.P (My University, 2005)
This prospective study was carried out at the Castle Street Hospital for Women (CSHW) during period of six (6) months from January to June 2005 . A total of 170 cases of readmissions were reported, but due to poor recording only 159 cases of readmissions was been able to analyze. The other prospective study was carried out at near by peripheral health care institutes manage by Colombo Municipal Council (Maternity Homes) and at Base Hospital Homagama. The objective of the study was to determine Socio-demographic characters of the readmissions, to identify causes of readmissions of the mothers and patients, to identify complications arising from medical or surgical management and to make recommendations to minimize the readmissions. This study showed that most of the Obstetric and Gynecology readmissions were due to infections and most are from urbanized area residing population. The infection percentage observed in Lower Segment Caesarean Section (LSCS) were high with use of Intra Venous and oral antibiotics. In mutipara there were more incidents of late post partum hemorrhages (PPH). The prospective study confirm that there is a percentage of population seeking medical and surgical treatment from near by peripheral health care institutes for minor events